2011
DOI: 10.1007/s00701-011-1157-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the subthalamic nucleus versus the zona incerta in the treatment of essential tremor

Abstract: In this limited material, STN DBS was demonstrated to be an efficient treatment for ET, even though cZi DBS was more efficient. The STN may be an alternative target in the treatment of ET, pending further investigations to decide on the relative merits of the different targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 17 publications
2
34
0
4
Order By: Relevance
“…Particularly the stimulation of the caudal component of the Zi [50,51] seems to provide a greater therapeutic benefit compared to the stimulation of the Stn, the currently preferred target structure for PD [21]. Several studies suggested that cZi nucleus is effective in suppressing tremors of various etiologies of both the distal and proximal extremities [52][53][54]. a recent study comparing DBS of the Stn and the Zi found similar results for the motor function but specific improvement in anxiety and Table 3 average signal-to-noise ratios (Snr) and contrast-to-noise ratios (cnr) of the zona incerta for each sequence to balance the differences of the vendor optimised sequences in slice thickness and pixel size the measured Snr and cnr values were adjusted to a voxel of 1 x 1 x 1 mm³ c Sequences with a statistically significant superior SNR and CNR values compared to T2-FLAIR imaging (paired t-test) are denoted (*) self-reported depression for Zi stimulation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly the stimulation of the caudal component of the Zi [50,51] seems to provide a greater therapeutic benefit compared to the stimulation of the Stn, the currently preferred target structure for PD [21]. Several studies suggested that cZi nucleus is effective in suppressing tremors of various etiologies of both the distal and proximal extremities [52][53][54]. a recent study comparing DBS of the Stn and the Zi found similar results for the motor function but specific improvement in anxiety and Table 3 average signal-to-noise ratios (Snr) and contrast-to-noise ratios (cnr) of the zona incerta for each sequence to balance the differences of the vendor optimised sequences in slice thickness and pixel size the measured Snr and cnr values were adjusted to a voxel of 1 x 1 x 1 mm³ c Sequences with a statistically significant superior SNR and CNR values compared to T2-FLAIR imaging (paired t-test) are denoted (*) self-reported depression for Zi stimulation [55].…”
Section: Discussionmentioning
confidence: 99%
“…However, this 3.2% represents only one procedure at one surgical center. There is currently limited evidence supporting the use of STN-targeted DBS for ET [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…The ZI, an embryological derivate of the ventral thalamus, is a small horizontally elongated area of grey matter cells in the subthalamic region of the mesencephalon. The nucleus gains increasing importance as an alternative target for the treatment with DBS of various neurological and psychiatrical disorders including ET and PD [12,13] . It is located at the base of the dorsal thalamus and separates the lenticular fasciculus from the thalamic fasciculus ("field H1 and H2 of Forel") [14,15] .…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%